THE PUBLISHING ASSOCIATION “ŠALTINIS” - PETREIKIS, TOMAS PETREIKIS (Knygotyra, 2015)
The dean of Plungė V. Jarulaitis and his entourage started actively organising Catholic Lithuanian book publishing after the Lithuanian press ban. A project of a Lithuanian Catholic publishing organization establishment was originated with the lower clergy reaches. That project was implemented on July 17, 1905. The publishing association “Šaltinis” was established in Plungė. The structure of the association was created, publishing plans and financial reserve were also anticipated. The association was stock and it was run by a chairman and priest V. Jarulaitis and his assistant J. Bikinas, who was also a priest. The association was specialized in publishing popular religious literature. The association “Šaltinis” functioned surreptitiously. Only its members, associates and the hierarchs of the Samogitian see knew about that association. The publishing centre actively massed the intellectual power. The vast majority of nationally conscious priests from the Samogitain region belonged to the association. In those days the eminent participants of Lithuanian National Revival such as J. Tumas-Vaižgantas, a poet J. Šnapštys, a writer Šatrijos Ragana and others belonged to the association “Šaltinis”. The association showed accomplished work, P. Turauskas’ and Šnapštys’ translations were made ready and they continued the other editions though a Samogitian bishop M. Paliulionis for his personal reasons moved the association “Šaltinis” to Kaunas. On October 12, 1905 the organization was reorganized and initiated Saint Kazimieras association creation. Plungė lost a part of Catholic book publishing centre and the association had problems in Kaunas. The shown example of the association “Šaltinis” inspired the further organizational Catholic publishing tone, which was continued by Saint Kazimieras association.